Personal finance : building your future - Walker, Robert B.; Walker, Kristy P. (New York : McGraw-Hill Education, 2017)
"Personal Finance, 2e by Walker/Walker offers students an engaging treatment of personal finance, while incorporating unique themes, an application-driven pedagogy, and a definitive action plan. Unlike other texts on the market, it offers a frank and timely discussion of living within one's means and incorporating personal values and priorities into a personal financial plan. The intent is to help readers set priorities that guide their finances, rather than the other way around. This book establishes a path toward financial freedom that is less about accumulating wealth and more about building a future tailored to individual goals. With Walker/Walker, your future looks bright!"--
Revised edition of the authors' Personal finance, 2013.
Includes index.
BBS
Keywords: Finance, Personal; Business & finance